SEASONAL ACTIVITY AND SUSCEPTIBILITY OF SOME POTATO VARIETIES TO INFECTION BY TOMATO LEAFMINOR Tuta absoluta (Meyrick) AND THE OTHER PESTS OF ARTHROPODS - Nabil Almallah (Mesopotamia Journal of Agriculture)
ABSTRACT The study showed to testing susceptibility of some Potato varieties univresa, safran, Alaska, Revira,Alaadin, Borin in Ninevah Governorate during the year 2011 to infection by Tomato leafminor and other Arthropod pests was infected in different degrees with Tomato leafminor Tuta abosluta (Meyrick), colorado beetle Leptinotarsa decimelineuta(say), green peach aphid myzus persicae (sulzer) Potato aphid Macrosiphum euphorbiae (Thomas),leafhoppers Empoasca spp, whitefly Bemisia tabac! Gen and red mite Tetranychus urticae Koch, the general mean numbers of these pests was oscilliating during eight period for taking samples (from 17/4 to 8/6) which reached respectively 6.52, 10.56, 3.18, 2.23, 4.07,1.11, 1.33, 13.54 individual/50 leave, the first appearance of whitfly and red mite was on 8/6 on all potato varieties. The general mean numbers of these pests on varieties universa, safran, Alaska, Revira, Alaaldin and Borin was 11.4, 3.05, 3.78, 4.01, 2.96, 6.49 individual/50 leave respectively. the numbers of leafhoppers was the highest significanlty 10.81 individual/50 leave. accrording to pest density parameter(individual/ 50 leaves) the highest sensitivity with infection of Tomato leafminor, Colorado beetle, leafhoppers, peach Aphid, Potato Aphid, whitefly and red mite were Revira, universa, universa, universa, universa,Borin, Borin respectively which reached 3.83, 25.19, 20.59, 4.08, 7.75, 5.52,93.75: respectively.